1993
DOI: 10.1627/jpi1958.36.467
|View full text |Cite
|
Sign up to set email alerts
|

Deep Desulfurization of Light Oil (Part 1) Hydrodesulfurization of Methyl-substituted Benzothiophenes and Dibenzothiophenes in Light Gas Oil.

Abstract: In deep hydrodesulfurization (HDS) of polyaromatic sulfur-containing compounds in light gas oil catalyzed by Co-Mo/Al2O3, the behavior of methyl-substituted benzothiophenes, monomethyldibenzothiophenes (C1-DBTs) and dimethyldibenzothiophenes (C2-DBTs) was traced under the following could be 2,3,7-trimethylbenzothiophene. The conversions of C1-DBTs other than 4-methyldibenzothiophene (4-MDBT) were very close to the conversion of nonsubstituted DBT.The behavior of three kinds of C2-DBTs other than 4,6-dimethyldi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 0 publications
3
7
1
Order By: Relevance
“…Thirdly is the type of sulfur compound, activation energy for total sulfur almost higher than individual, Steinner and Blekkan [14] found that the activation energy for total sulfur of light gas oil is (119.966) KJ/mol depending on contains of sulfur compound in oil. For present study these results disagree with Kabe et al [15] who found (100.32) KJ/mol for DBT, this comparison with the same individual sulfur compound.…”
Section: Activation Energycontrasting
confidence: 99%
“…Thirdly is the type of sulfur compound, activation energy for total sulfur almost higher than individual, Steinner and Blekkan [14] found that the activation energy for total sulfur of light gas oil is (119.966) KJ/mol depending on contains of sulfur compound in oil. For present study these results disagree with Kabe et al [15] who found (100.32) KJ/mol for DBT, this comparison with the same individual sulfur compound.…”
Section: Activation Energycontrasting
confidence: 99%
“…4,6-DMDBT must compete for the hydrogenation active site with aromatic partners of dominant presence in the gas oil as observed in previous , and the present studies. Hence, the selective hydrogenation of 4,6-DMDBT is very essential to accelerate its desulfurization.…”
Section: Discussionsupporting
confidence: 79%
“…To elucidate the HDS mechanisms of such dibenzothiophenes as 4-MDBT and 4,6-DMDBT, we previously examined the reaction kinetics of these compounds in detail (Kabe et al, 1993a;Zhang et al, 1996). Some groups have also reported the retention of 4-MDBT and 4,6-DMDBT even under deep desulfurization conditions and have demonstrated that the HDS rates were remarkably retarded only by substitution at the 4-and 6-positions of DBT (Kabe et al, 1992(Kabe et al, , 1993bAmorelli et al, 1992;Ma et al, 1994). However, the kinetics of DBTs in HDS of light gas oil, and especially of 4-MDBT and 4,6-DMDBT, have largely been ignored.…”
Section: Introductionmentioning
confidence: 99%